THE IMPLEMENTATION OF THE SCIENTIFIC APPROACH IN DEVELOPING STUDENTS' SPEAKING SKILL - Gianisa Putri Miftari, - (2019)
The term "Scientific Approach" (SA) gained its popularity in the field of education in Indonesia when Curriculum 2013 was launched by Ministry of Education and Culture in 2013. Through The Scientific Approach, the learners are given the chance to construct their understanding based on the stages of observing, questioning, experimenting, associating and communicating (Kemdikbud, 2013). This research was aimed at describing the use of SA in helping students to develop their speaking skill. The qualitative method was employed in this research in order to investigate the process of SA in helping students to develop their speaking skill. The data were obtained through classroom observation, students' works, and students' reflections. The result of the research revealed that the implementation of SA could help eighth grade students to develop their speaking skill by applying the appropriate strategies in each stage. Out of five stages, the activities in observing, questioning, experimenting, and communicating were showing a strong impact. Meanwhile, the impact of the activities in associating stage was not really significant. In addition, the students admitted that the various activities provided in SA were interesting, so that they enjoyed the whole lesson.